PRR11 promotes cell proliferation by regulating PTTG1 through interacting with E2F1 transcription factor in pan-cancer - Zhang, Haibo; He, Ziqing; Qiu, Li; Wei, Jinfen; Gong, Xiaocheng; Xian, Mingjian; Chen, Zixi; Cui, Ying; Fu, Shuying; Zhang, Zihao; Hu, Bowen; Zhang, Xiquan; et al. (Frontiers in Molecular Biosciences, 2022)
The upregulated proline rich 11 (PRR11) plays a critical role in cancer progression. The relevant biological functions of PRR11 in pan-cancer development are not well understood. In the current study, we found that PRR11 was upregulated in 19 cancer types compared with that of normal tissues and high-expressed PRR11 was a predictor of poor prognosis in 10 cancer types by bioinformatics. Then we showed that interfering PRR11 on three cancer cell lines could greatly inhibit cell proliferation and migration and arrest cells to S phase in vivo. Based on RNA-seq, downregulation of PRR11 expression could extremely suppress the expression of PTTG1 and the cell cycle pathway identified by a differentially expressed gene analysis and an enrichment analysis. The expression of PRR11 and PTTG1 was positively correlated in TCGA and independent GEO data sets. Importantly, we revealed that the PRR11 could express itself in the nucleus and interact with E2F1 on the PTTG1 promoter region to increase the expression of PTTG1. Further results indicated that the expression of PTTG1 was also associated with poor prognosis in 10 cancer types, while downregulation of PTTG1 expression could inhibit cancer cell proliferation and migration. Therefore, we found that PRR11 served as an oncogene in pan-cancer and could influence the cell cycle progression through regulating the expression of PTTG1 by interacting with the transcription factor E2F1.